1991
DOI: 10.1177/002221949102400908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reading and Writing on Cerebral Laterality in Good Readers and Children with Dyslexia

Abstract: The present study evaluated the idea that the hemisphere-specific cognitive demands of reading and writing may induce task-specific maladaptive patterns of language lateralization in children with dyslexia. Situation-specific lateralization was examined in a repeated measures design under three dichotic listening conditions: baseline, concurrent reading, and concurrent writing. Twelve males with phonological dyslexia, 8 to 12 years old, were compared to 12 age-matched and 12 younger reading-matched good reader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Mather, 2001). For example in two dichotic listening studies that involved reporting different digits delivered simultaneously to each ear, children with dyslexia differed from controls in producing a decrease in LH lateralization for written but not oral reports (Kershner, Henninger, & Cooke, 1984; Kershner & Stringer, 1991). This decrease correlated with phonological decoding difficulties with real words and pronounceable nonwords.…”
mentioning
confidence: 99%
“…Mather, 2001). For example in two dichotic listening studies that involved reporting different digits delivered simultaneously to each ear, children with dyslexia differed from controls in producing a decrease in LH lateralization for written but not oral reports (Kershner, Henninger, & Cooke, 1984; Kershner & Stringer, 1991). This decrease correlated with phonological decoding difficulties with real words and pronounceable nonwords.…”
mentioning
confidence: 99%
“…Along the same lines, dyslexics have been found to make more CV identification errors in written than in oral expression (Lieberman, Meskill, Chattillon, & Schupack, 1985) and in dichotic digit listening, children conforming to the WW subtype differ from controls and the LL subtype in switching from a right ear/LH advantage for oral responses to a left ear/RH advantage for written responses, due primarily to poorer right ear recall (Kershner, Henninger, & Cooke, 1984;Kershner & Stringer, 1991). Further, pseudoword writing slows the pen speed of WW dyslexics but speeds that of the LL subtype (Seymour, 1987)-the latter result consistent with the strong right ear advantage demonstrated by this subtype in dichotic CV listening (Cohen, Hynd, & Hugdahl, 1992)-and WW dyslexics are less dextral and LL dyslexics more dextral than controls on measures of hand preference and skill (Annett, Eglinton, & Smythe, 1996).…”
mentioning
confidence: 99%
“…Performance on directed attention dichotic tasks discriminates between groups of learning disabled children and both age and reading matched controls (Asbjørnsen & Bryden, 1998;Bakker & Kappers, 1988;Boliek, Obrzut, & Shaw, 1988;Helland & Asbjørnsen, 2000, 2001Hiscock & Kinsbourne, 1982;Hugdahl, Ellertsen, Waaler, & Kløve, 1989;Hynd, Obrzut, Weed, & Hynd, 1979;Kershner & Graham, 1995;Kershner & Micallef, 1991;Kershner & Micallef, 1992;Kershner & Morton, 1990;Obrzut, 1988;Obrzut, Boliek, & Bryden, 1997;Obrzut, Conrad, Bryden, & Boliek, 1988;Obrzut, Horgesheimer, & Boliek, 1999;Obrzut, Hynd, & Obrzut, 1983;Obrzut, Hynd, Obrzut, & Leitgeb, 1980). Few studies have addressed how DL performance could be related to the reading impairment per se and/or additional cognitive impairment (Bakker & Kappers, 1988;Kershner, Henninger, & Cooke, 1984;Kershner & Micallef, 1991;Kershner & Stringer, 1991), or whether DL performance could identify subgroups of learning disabled children (Obrzut, Hynd, & Obrzut, 1983). Obrzut, Hynd, and Obrzut (1983) found that the directed dichotic tasks contributed the most of a total of 13 cognitive neuropsychological tasks to the discrimination between learning disabled and normal reading children in a stepwise discriminant function analysis.…”
mentioning
confidence: 99%